Flavour evaluation of chocolate formulated from cocoa beans from different countries - Jinap, S.; Dimick, P.S.; Hollender, R. (Elsevier Science, 1995)
Flavour characteristics of the chocolate made from 14 dried, fermented cocoa bean samples from eight different countries of origin and the relationship with pH, titratable acidity and acetic and lactic acid were studied. The fermented dried cocoa beans were processed into semi-sweet dark chocolate and were evaluated for their flavour difference by the multiple comparison test using the Ghanaian sample as a reference. The descriptors and the intensities of the chocolate flavour perceived by the taste panel members were also obtained. There was no correlation between the flavour score and the pH, tritratable acidity, acetic and lactic acid concentrations. The study found that chocolate samples made from the low pH (4.75-5.19) and high pH (5.50-5.80) cocoa beans have low response in strong chocolate flavour. On the other hand, chocolate samples made from the Ghanaian and Nigerian beans which have medium pH values of 5.20-5.49 received a high response in strong chocolate flavour. More off-flavour descriptors were perceived from chocolate samples made from low-pH cocoa beans.